The Euphemistic Expressions in EFL Classrooms: Teacher Strategies in Instructional Communication - Muhsin, Muh Arief; Idrus, Muhammad Alif; Ilmiah; Fontillas, Lemuel; Latiff, Azmi Abdul; Ergasheva, Guli (English Department, Universitas Negeri Surabaya, 2025)
Euphemistic expressions play a significant role in educational discourse, particularly in English as a Foreign Language (EFL) classrooms where cultural sensitivity and affective support are central to learning. This study investigates how English teachers in Indonesia strategically use euphemism to manage classroom interaction and provide feedback without threatening students’ self-esteem. A qualitative descriptive design was employed, focusing on two secondary school English teachers in South Sulawesi. Data were collected through non-participant classroom observations, with detailed field notes capturing authentic teacher–student exchanges, and were validated through post-lesson clarification. Thematic analysis revealed seven recurrent categories of euphemistic strategies: politeness markers, softening language, downplaying language, indirect requests, minimization of errors, correction with positive feedback, and reassurance. These strategies were not merely linguistic substitutions but pedagogical tools for fostering respectful communication, reducing anxiety, and sustaining learner engagement. Findings suggest that euphemism contributes to the affective dimension of language pedagogy by aligning instructional clarity with socio-cultural expectations of respect and harmony. The study highlights the importance of integrating euphemistic strategies into teacher education and professional development. While limited in scope, it provides a foundation for further research on the pragmatic and pedagogical functions of euphemism in EFL contexts.